Conventional microscopy vs. computer imagery in chiropractic education. - Cunningham CM; Larzelere ED; Arar I (Journal of Chiropractic Education (Association of Chiropractic Colleges))
Purpose: As human tissue pathology slides become increasingly difficult to obtain, other methods of teaching microscopy in educational laboratories must be considered. The purpose of this study was to evaluate our students' satisfaction with newly implemented computer imagery based laboratory instruction and to obtain input from their perspective on the advantages and disadvantages of computerized vs. traditional microscope laboratories. Methods: This undertaking involved the creation of a new computer laboratory. Robbins and Cotran Pathologic Basis of Disease, 7th ed,was chosen as the required text which gave students access to the Robbins Pathology website, including complete content of text, Interactive Case Study Companion, and Virtual Microscope. Students had experience with traditional microscopes in their histologyand microbiology laboratory courses. Student satisfaction with computer based learning was assessed using a 28 question survey which was administered to three successive trimesters of pathology students (nD193) using the computer survey website Zoomerang. Answers were given on a scale of 1-5 and statistically analyzed using weighted averages. Results: The survey data indicated that students were satisfied with computer based learning activities during pathology laboratory instruction. The most favorable aspect to computer imagery was 24-7 availability (weighted avg. 4.16), followed by clarification offered by accompanying text and captions (weighted avg. 4.08). Conclusion: Although advantages and disadvantages exist in using conventional microscopy and computer imagery, current pathology teaching environments warrant investigation of replacing traditional microscope exercises with computer applications. Chiropractic students supported the adoption of computer-assisted instruction in pathology laboratories.